Effect of Molasses and Three Sources of Local Microorganism Inoculants (MOL) on Microorganism Population, Growth and Productions of Mustard Greens (Brassica rappa var. parachinensis L.) - Nur Indah Sari (AGRONISMA, 2022)
Manure is a waste product from livestock that can be used as a nutrient addition, improving the physical, chemical and biological properties of the soil. Each ton of manure contains 5 kg N, 3 kg P2O5 and 5 kg K2O as well as other essential nutrients in relatively small amounts (Hardjowigeno, 2003). Molasses is a by-product of the cane sugar processing industry. Molasses contains organic compounds in the form of sugars such as sucrose, glucose and fructose. The sugar content is useful as a carbon source for microorganisms. The presence of crude protein and amino acids is a useful source of nitrogen for the growth of local microorganisms (MOL) (Sebayang, 2006). The MOL solution contains macro and micro nutrients, also contains bacteria that have the potential to decompose organic matter, stimulate growth and act as agents for controlling plant pests and diseases. The design used is factorial RAL. The results showed that the source of cow dung inoculants with a concentration of 20% molasses had the highest population of soil bacteria and the source of goat dung inoculants with a concentration of 30% molasses had the highest population of soil fungi. Goat dung inoculants with 50% molasses concentration and cow dung inoculants with 40-50% molasses concentration showed the best results on the growth and chlorophyll content of mustard plants. The source of cow dung inoculants with 40% molasses concentration showed the best mustard plant yields.